Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To rewrite the quadratic function [tex]\( f(x) = x^2 + 4x + 41 \)[/tex] by completing the square, we need to transform it into the form [tex]\( f(x) = (x + a)^2 + b \)[/tex]. Here are the steps:
1. Identify and group the [tex]\( x \)[/tex]-terms:
[tex]\[ f(x) = x^2 + 4x + 41 \][/tex]
2. To complete the square, we first take the coefficient of [tex]\( x \)[/tex] (which is 4) and halve it:
[tex]\[ \frac{4}{2} = 2 \][/tex]
3. Next, we square this value:
[tex]\[ 2^2 = 4 \][/tex]
4. Rewrite the function by adding and subtracting this square value inside the equation, ensuring that the function remains unchanged:
[tex]\[ f(x) = x^2 + 4x + 4 - 4 + 41 \][/tex]
5. Group the perfect square trinomial and calculate the remaining constant term:
[tex]\[ f(x) = (x + 2)^2 - 4 + 41 \][/tex]
6. Simplify the constant term:
[tex]\[ -4 + 41 = 37 \][/tex]
7. So the completed square form of the quadratic function is:
[tex]\[ f(x) = (x + 2)^2 + 37 \][/tex]
Thus, the quadratic function [tex]\( f(x) = x^2 + 4x + 41 \)[/tex] rewritten by completing the square is:
[tex]\[ f(x) = (x + 2)^2 + 37 \][/tex]
1. Identify and group the [tex]\( x \)[/tex]-terms:
[tex]\[ f(x) = x^2 + 4x + 41 \][/tex]
2. To complete the square, we first take the coefficient of [tex]\( x \)[/tex] (which is 4) and halve it:
[tex]\[ \frac{4}{2} = 2 \][/tex]
3. Next, we square this value:
[tex]\[ 2^2 = 4 \][/tex]
4. Rewrite the function by adding and subtracting this square value inside the equation, ensuring that the function remains unchanged:
[tex]\[ f(x) = x^2 + 4x + 4 - 4 + 41 \][/tex]
5. Group the perfect square trinomial and calculate the remaining constant term:
[tex]\[ f(x) = (x + 2)^2 - 4 + 41 \][/tex]
6. Simplify the constant term:
[tex]\[ -4 + 41 = 37 \][/tex]
7. So the completed square form of the quadratic function is:
[tex]\[ f(x) = (x + 2)^2 + 37 \][/tex]
Thus, the quadratic function [tex]\( f(x) = x^2 + 4x + 41 \)[/tex] rewritten by completing the square is:
[tex]\[ f(x) = (x + 2)^2 + 37 \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.